2020
DOI: 10.1007/s00418-020-01887-5
|View full text |Cite
|
Sign up to set email alerts
|

Pcdh18a regulates endocytosis of E-cadherin during axial mesoderm development in zebrafish

Abstract: The notochord defines the axial structure of all vertebrates during development. Notogenesis is a result of major cell reorganization in the mesoderm, the convergence and the extension of the axial cells. However, it is currently not fully understood how these processes act together in a coordinated way during notochord formation. The prechordal plate is an actively migrating cell population in the central mesoderm anterior to the trailing notochordal plate cells. We show that prechordal plate cells express Pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…To investigate the possible involvement of Pcdh18a in SCP emigration from the somites, we firstly used an antisense morpholino (MO). Previous studies found that morpholinos blocking Pcdh18a translation caused defects in the early development of zebrafish embryos and lethality by mid-somitogenesis (Aamar and Dawid, 2008;Bosze et al, 2020). We found that a splice-blocking MO targeting the intron1-exon2 (i1e2) junction of nascent pcdh18a RNA led with high efficiency to retention of intron 1 in the mRNA (Fig.…”
Section: The Cytoplasmic Domain Of Pcdh18a Is Involved In Stromal Cel...mentioning
confidence: 67%
“…To investigate the possible involvement of Pcdh18a in SCP emigration from the somites, we firstly used an antisense morpholino (MO). Previous studies found that morpholinos blocking Pcdh18a translation caused defects in the early development of zebrafish embryos and lethality by mid-somitogenesis (Aamar and Dawid, 2008;Bosze et al, 2020). We found that a splice-blocking MO targeting the intron1-exon2 (i1e2) junction of nascent pcdh18a RNA led with high efficiency to retention of intron 1 in the mRNA (Fig.…”
Section: The Cytoplasmic Domain Of Pcdh18a Is Involved In Stromal Cel...mentioning
confidence: 67%
“…A question remains however: what is driving the movement of following cells? It was recently established that a group of cells, located just posterior to the polster, expresses pcdh18a , which, by modulating E-cadherin recycling, would transform them into a fast-migrating group (Bosze et al, 2020) which represents an attractive candidate to guide polster migration. If true, this, however, only shifts the question to how these cells are oriented towards the animal pole.…”
Section: Discussionmentioning
confidence: 99%
“…Despite several differences with vertebrate anatomy and genoarchitecture, this six3/6 + region may represent the amphioxus homologue of the prechordal plate (Albuixech-Crespo et al, 2017). In vertebrates, notochord formation from axial mesoderm requires the complex orchestration among active migration of prechordal cells (Bosze et al, 2020), non-canonical Wnt11-mediated cellular movements of paraxial mesoderm (Heisenberg et al, 2000), and CE of deep neural cells (Keller and Sutherland, 2020). Treatment with SP600125 also inhibits the mediolateral cell intercalation of the neurectoderm required for axial elongation in the annelid Platynereis dumerilii (Steinmetz et al, 2007).…”
Section: Jnk Plays a Conserved Role In Gastrulation And Convergence Extension Movementsmentioning
confidence: 99%